Technical and Conceptual Considerations for Performing and Interpreting Functional MRI Studies in Awake Rats - Febo, Marcelo (Frontiers in Psychiatry, 2011)
Functional neuroimaging studies in rodents have the potential to provide insight into neurodevelopmental and psychiatric conditions. The strength of the technique lies in its non-invasive nature that can permit longitudinal functional studies in the same animal over its adult life. The relatively good spatial and temporal resolution and the ever-growing database on the biological and biophysical basis of the blood oxygen level dependent (BOLD) signal make it a unique technique in preclinical neuroscience research. Our laboratory has used imaging to investigate brain activation in awake rats following cocaine administration and during the presentation of lactation-associated sensory stimuli. Factors that deserve attention when planning fMRI studies in rats include technical issues, animal physiology and interpretability of the resulting data. The present review discusses the pros and cons of animal imaging with a particular focus on the technical aspects of studies with awake rats. Overall, the benefits of the technique outweigh its limitations and the rapidly evolving methods will open the way for more laboratories to employ the technique in neuroscience research.